DE-PASS Best Evidence statement (BESt): A systematic review and meta-analysis on the effectiveness of trials on device-measured physical activity and sedentary behaviour and their determinants in children aged 5-12 years - Bartoš, F.; Brandes, M.; Capranica, L.; Carlin, A.; Ciaccioni, S.; Corvino, C.; Cortis, C.; di Credico, A.; Drid, P.; Gallè, F.; Izzicupo, P.; Jahre, H.; et al. (Sports Medicine, 2025)
Background: To combat the high prevalence of physical inactivity among children, there is an urgent need to develop and implement real-world interventions and policies that promote physical activity (PA) and reduce sedentary behaviour (SB). To inform policy makers, the current body of evidence for children`s PA/SB interventions needs to be translated. Objectives: The current systematic review and meta-analysis aimed to identify modifiable determinants of device-measured PA and SB targeted in available intervention studies with randomized controlled trial (RCT) and controlled trial (CT) designs in children and early adolescents (5-12 years) and to quantify the effects of the interventions within their respective settings on the determinants of PA/SB and the outcomes PA and SB. Methods: A systematic search was conducted in MEDLINE, PsycINFO, Web of Science, SPORTDiscus and CENTRAL. Studies were considered if they were randomized controlled trials (RCTs) or controlled trials (CTs), included children and/or early adolescents (5-12 years; henceforth termed children), measured PA and/or SB using device-based methods and measured PA and/or SB and determinants of PA/SB at least at two timepoints. Risk of bias was assessed using the Cochrane Risk of Bias Tool for Randomised Trials (RoB2) for RCTs and Risk of Bias in Non-randomised Studies of Interventions (ROBINS-I) for CTs. The quality of the generated evidence was assessed using Grading of Recommendations Assessment, Development and Evaluation (GRADE). Robust Bayesian meta-analysis was conducted to quantify the effects of the interventions on the determinants of PA/SB, and the outcomes PA and SB, stratifying by study design, duration of PA/SB measurement, intervention setting and duration of follow-up measurement. Study characteristics and interventions were summarized. Results: Thirty-eight studies were included with a total sample size of n = 14,258 (67% girls). Settings identified were school, family/home, community and combinations of these. The review identified 38 modifiable determinants, spanning seven categories on individual, interpersonal and physical environmental levels, with 66% of determinants on the individual level. Overall, the results indicated trivial-to-moderate effects of the interventions on the determinants of PA and SB, with mostly trivial level of evidence for the presence of an effect (as indicated by a small Bayes factor; BF10 < 3.00). The exceptions were moderate effects on parental PA modelling in the family/home setting and SB measured during specific parts of the school day. Higher quality of evidence was found in the family/home setting compared with other settings. Discussion: Overall, the results indicated that interventions have neither been effective in modifying the determinants of PA/SB, nor changing the PA/SB outcomes in children. In general, the approach in the current review revealed the breadth of methodological variability in children`s PA interventions. Research is needed to address novel approaches to children`s PA research and to identify potential determinants to inform policy and future interventions.